(untitled) (Reflection and Critique Law Magazine, 2020)
The present study aims to demonstrate the main difficulties present in the prisons, in which the condemned detainee prevails. In this sense, the present work will demonstrate the history of prisons since antiquity, as well as prison systems, the precariousness of Brazilian prisons, the overcrowding of prisons showing data of overcrowding, factions’ powers, and other factors that lead to overcrowding with the aim of showing how their human dignity is harmed and critically analyzing that the prison is not exercising its function of re-socializing the condemned person. To show the poor conditions of the prison that facilitate the strengthening of the criminal factions, as well as the criminalization in which we live, being a country that becomes increasingly violent, since the violence today is present in all the scopes. Demonstrate the insufficiency of the Public Power, since the increase of crime is linked to the action and omission of the State, based on the decisions of the STF. The fundamental rights of the condemned who are expressed in the Federal Constitution are not being fulfilled, much less the precepts established in the Criminal Execution Law.